Does IL-17 Respond to the Disordered Lung Microbiome and Contribute to the Neutrophilic Phenotype in Asthma?. (28th January 2016) - Yang, Xu; Jiang, Yunqiu; Wang, Changzheng
Abstract : Th17/IL-17 plays an important role in host defense and hyperimmune responses against pathogenic bacteria accompanied by the recruitment of neutrophils. Th17-associated immune response is also involved in the pathogenesis of asthma, which is known as a noninfectious allergic airway disease and has been shown to be heterogeneous. Th17-associated inflammation usually contributes to the neutrophilic phenotype, which is often characterized by greater severity, airflow obstruction, and steroid resistance. Concurrently, advanced culture-independent molecular techniques have increased our understanding of the lung microbiome and demonstrated that disorders of the lung microbiome, including changes of the total burden, diversity, and community composition, may contribute to severe, treatment-resistant neutrophilic asthma, although the precise mechanism is still unclear. Because Th17/IL-17 plays a role in bacteria-mediated immune responses and is involved in neutrophilic asthma, there may be a link between them. We review the effects of Th17/IL-17 on bacteria and asthma, showing the possibility that Th17/IL-17 may be a key player in neutrophilic asthma which may be characterized as severe or treatment-resistant by responding to the disordered lung microbiome.